Scientific views of professor I. I. Gorelik on the problem of economy of criminal legal impact - Bakhur, Oleg I.; Kovalchuk, Aleksey V. (Journal of the Belarusian State University. Law, 2021)
The article illustrates the scientific views of I. I. Gorelik on the problem of saving criminal law impact. The relations of the professor’s ideas with the state former and current criminal legislation is made. It is argued that expressed by I. I. Gorelik law enforcement approaches to the qualification of crimes against human life and health correspond to the principle of economy of criminal law repression and the implementation of the principle of justice. It is substantiated that the professor’s proposals are in demand in science and law enforcement practice and await their development in scientific publications of other researchers, as well as implementation in the criminal legislation of the Republic of Belarus.